1996
DOI: 10.1074/jbc.271.46.29446
|View full text |Cite
|
Sign up to set email alerts
|

The Disulfide Bond Structure of Plasmodium Apical Membrane Antigen-1

Abstract: Apical membrane antigen-1 (AMA-1) of Plasmodium falciparum is one of the leading asexual blood stage antigens being considered for inclusion in a malaria vaccine. The ability of this molecule to induce a protective immune response has been shown to be dependent upon a conformation stabilized by disulfide bonds. In this study we have utilized the reversed-phase high performance liquid chromatography of dithiothreitol-reduced and nonreduced tryptic digests of Plasmodium chabaudi AMA-1 secreted from baculovirus-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
208
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(216 citation statements)
references
References 26 publications
4
208
0
4
Order By: Relevance
“…Using a conditional expression system in T. gondii, Mital et al (28) confirmed that AMA1 plays a role in the later stages of host cell invasion and obtained evidence that it may mediate regulation of rhoptry discharge. Determination of the x-ray crystal structure of AMA1 of P. vivax (PvAMA1) (29) and P. falciparum (PfAMA1) (30) confirmed previous indications (31) that the AMA1 ectodomain comprises three disulfide-constrained domains and showed that two of these (domains I and II) form PAN modules, often implicated in protein-protein and protein-carbohydrate interactions. Consistent with this, two reports have suggested an erythrocyte-binding role for AMA1 (32,33).…”
supporting
confidence: 60%
“…Using a conditional expression system in T. gondii, Mital et al (28) confirmed that AMA1 plays a role in the later stages of host cell invasion and obtained evidence that it may mediate regulation of rhoptry discharge. Determination of the x-ray crystal structure of AMA1 of P. vivax (PvAMA1) (29) and P. falciparum (PfAMA1) (30) confirmed previous indications (31) that the AMA1 ectodomain comprises three disulfide-constrained domains and showed that two of these (domains I and II) form PAN modules, often implicated in protein-protein and protein-carbohydrate interactions. Consistent with this, two reports have suggested an erythrocyte-binding role for AMA1 (32,33).…”
supporting
confidence: 60%
“…The AMA1 ectodomain, which is the vaccine target, is shed as 44 and 48 kDa alternate antigens before the parasite enters the red cell [5,10]. The ectodomain has 16 cysteine residues that form disulphide bonds to divide the antigen's tertiary structure into three different but interactive domains [11]. …”
Section: Introductionmentioning
confidence: 99%
“…This created both a 5Ј truncation and a 142-base pair internal deletion that resulted in the loss of multiple conserved cysteines thought to be important for protein folding (Hodder et al, 1996). AMA1/AMA1-myc parasites were transfected with the knockout construct.…”
Section: Generation Of the Conditional Knockoutmentioning
confidence: 99%
“…Since its initial discovery Ͼ15 years ago, AMA1 has received considerable attention as a malaria vaccine candidate (Deans et al, 1988;Collins et al, 1994;Anders et al, 1998;Kennedy et al, 2002;Stowers et al, 2002). AMA1 proteins are type I transmembrane proteins, with a short C-terminal cytoplasmic tail and a large N-terminal extracellular domain (ectodomain) containing 12-16 conserved cysteine residues (Waters et al, 1990;Hodder et al, 1996;Donahue et al, 2000;Hehl et al, 2000;Gaffar et al, 2004). Like other microneme proteins, AMA1 is secreted onto the parasite surface, where its ectodomain is proteolytically cleaved and shed (Narum and Thomas, 1994;Donahue et al, 2000;Hehl et al, 2000;Howell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%